Pesantren: Its Founding and Role in the Colonial Period - Ismah, Nor (Tebuireng: Journal of Islamic Studies and Society, 2022)
In Indonesia, Islamic education is still mostly provided through pesantren, or Islamic training institutions. They have a close relationship with tarekat, as they have been successful in maintaining Islam as a personal and compassionate faith rather than a cold and formal doctrine. Pesantrens changed throughout the colonial era from being a largely educational institution to a political organization that backed the independence fight. This article's objective is to look at how pesantren changed from being just educational institutions to considerably assisting in the fight for liberation, as well as how they contributed to the battle against Dutch colonialism. Using academic writing on pesantren that examines their position throughout the colonial era, the content in this piece was found through library research. This article makes the case that Java's colonialera social, cultural, and political protest groups benefited greatly from the pesantren system. It also seeks to explain their founding, objectives, student demographics, and involvement during this time period.